Analysis of the Use of Translation as a Learning Strategy in English - Hafizah Ismayati; Miftahul Jannah; Farida Repelita Waty Kembarent (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study looked at how students used translation-related strategies to learn English and their attitudes on the subject. Five English education majors were involved in this qualitative case study. The results showed that students thought of translation as a helpful part of their English language learning process. They also mentioned a range of translation-based learning exercises that fall under different learning approaches. It is anticipated that the study's conclusions will highlight and advise against the efficient use of translation in English language instruction for the benefit of pupils.